The Problematics of Research on Regional Theatre Conducted in Remote Areas - Coté, Jean-Guy; Leclercq, Marie-Claude; Lizé, Claude (Theatre Research in Canada / Recherches théâtrales au Canada, 1992)
In this paper, delivered to the Association for Canadian Theatre History during the Learned Societies Conference in May 1991, the Groupe de Recherche sur le Théâtre en Abitibi-Témiscamingue seeks to answer three questions concerning the problems posed by research on regional theatre conducted in remote areas: What is 'regional theatre'? Where does the current debate on the status of regional theatre originate? In what direction does this research appear to be heading? The answers to these questions must obviously take into account geographical factors such as the distance from major urban centres where theatrical activity, and research on that activity, are concentrated. But there are other factors as well, notably institutionalizing factors which militate against proper recognition of the role played by 'marginal'--as well as 'marginalized'--activity (amateur theatre, regional theatre, etc.) in the definition of the theatrical Institution itself. Dans cette communication présentée au Congrès des Sociétés savantes (colloque de l'Association d'histoire du théâtre au Canada) en mai 1991, le Groupe de recherche sur le théâtre en Abitibi-Témiscamingue répond à trois questions concernant la problématique de la recherche en région sur le théâtre régional: qu'est-ce que le théâtre régional? d'où origine le discours sur le théâtre régional? et où mènent ces recherches? Pour répondre à ces questions il faut tenir compte de facteurs géographiques, tel celui de la distance par rapport aux grands centres urbains où se concentrent l'activité théâtrale et la recherche sur le théatre; mais il faut surtout tenir compte de certains facteurs institutionnels qui bloquent la reconnaissance du rôle des pratiques marginales autant que marginalisées (théâtre amateur, théâtre régional...) dans la constitution de l'Institution elle-même.